Annual review of information technology developments for economic and social historians, 1993. - Middleton, Roger; Wardley, Peter (Economic History Review)
The article provides an overview of developments in information technology (IT) relevant to economic historians. General statistics packages have been selected for discussion. The authors also provide a brief overview of some major econometric software applications, a subset of particular interest to economic historians. The October 1989 survey of the journal "Economic History Review" revealed that statistical applications were the software packages most utilized by economic historians in undergraduate and postgraduate teaching in Great Britain. Technical developments associated with WINDOWS, the graphical-user interface for MS-DOS PCs, which has come to dominate the commercial environment, have stimulated the development of new and enhanced applications software which widens the potential of IT for teaching and research in economic history. For example, statistics and econometric applications are a particularly interesting example because they played an important role in the early diffusion of IT into economic history.